2011
DOI: 10.1007/s12356-011-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

A domain decomposition method for granular dynamics using discrete elements and application to railway ballast

Abstract: The paper is devoted to the development of a non overlapping domain decomposition method suited to granular dynamics. The formulation and the efficiency of such a method are well established for structural mechanics. In order to extend this approach to granular systems a so-called primal splitting of the domain is chosen because it is a less intrusive method for software development.Once the interface problem is defined and the solver is slightly enriched with some extra numerical parameters, the method is tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Several domain decomposition approaches have been proposed for contact problems, see [8,3,10,9,4,24,3] amongst others, but a few are concerned with multiple contacts in granular media (for an algebraic-like partition, see [17], and for a geometric partitioning of the discrete granular domain, see [5,2,23,30]). Here, we focus on the comparison of two formulations, one similar to FETI approaches, the other closer to additive Schwarz approaches, and of two implementations of the underlying communication scheme.…”
Section: Domain Decomposition Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several domain decomposition approaches have been proposed for contact problems, see [8,3,10,9,4,24,3] amongst others, but a few are concerned with multiple contacts in granular media (for an algebraic-like partition, see [17], and for a geometric partitioning of the discrete granular domain, see [5,2,23,30]). Here, we focus on the comparison of two formulations, one similar to FETI approaches, the other closer to additive Schwarz approaches, and of two implementations of the underlying communication scheme.…”
Section: Domain Decomposition Approachesmentioning
confidence: 99%
“…The overlapping is rendered by the lack of partition of the unity in (17) in comparison with (7). Here the domain partitioning defines a minimal overlapping between subdomains, since the dynamical operators M E , for E = 1, ..., n sd duplicate the contribution of the interface grains.…”
Section: Schwarz-like Domain Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that shape of the grains is of extreme importance [8]. Therefore, complex and realistic shapes are often used in simulation, for example discrete ellipsoids [4], tetrahedrons [18], polyhedrons [1,5] or clumps of smaller spherical particles [6,7,17].…”
Section: Introductionmentioning
confidence: 99%